THE HEART OF NURSING: EMOTIONAL INTELLIGENCE EXPLORED - Emily , A. Collins (Research Journal of Health, Medicine and Nursing, 2024)
Emotional Intelligence (EI) has gained recognition as a vital component of human cognition and behavior. Initially conceptualized by Salovey and Mayer in 1990, EI encompasses the capacity to accurately perceive and express emotions, as well as employ emotions for motivation, planning, and goal achievement. EI has established itself as an essential tool in various fields, such as education, psychology, and business, contributing to team cohesion, effective communication, leadership development, and productivity. Over time, different models of EI have emerged, providing various perspectives on this construct. These models include the skills model, which views EI as a malleable cognitive ability, the personality model, which considers EI a stable facet of one's character, and the mixed model, which combines abilities and personality traits in defining EI. Some experts propose that EI, distinct from traditional cognitive intelligence (IQ), represents another form of cognition that integrates emotions and can significantly enhance academic or professional performance. This paper explores the multifaceted nature of EI and its relevance in contemporary society. By investigating the different models of EI, it aims to contribute to a deeper understanding of the roles emotions play in human intelligence and behavior.